2021
DOI: 10.1186/s12874-021-01385-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical researchers’ lived experiences with data quality monitoring in clinical trials: a qualitative study

Abstract: Background Fundamental to the success of clinical research that involves human participants is the quality of the data that is generated. To ensure data quality, clinical trials must comply with the Good Clinical Practice guideline which recommends data monitoring. To date, the guideline is broad, requires technology for enforcement, follows strict industry standards, mostly designed for drug-registration trials and based on informal consensus. It is also unknown what challenges clinical trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In a recent qualitative study, Australian clinical researchers expressed a lack of guidance, education, and training in relation to data management and monitoring. 5 This study suggested that clinical data managers in both academic and industry settings have received either on-the-job training or self-paced learning focusing on specific work procedures. This doesn't necessarily mean that GCP training was not conducted.…”
Section: Recruitment Training and Education Of Australian Clinical Data Management/data Science Professionalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent qualitative study, Australian clinical researchers expressed a lack of guidance, education, and training in relation to data management and monitoring. 5 This study suggested that clinical data managers in both academic and industry settings have received either on-the-job training or self-paced learning focusing on specific work procedures. This doesn't necessarily mean that GCP training was not conducted.…”
Section: Recruitment Training and Education Of Australian Clinical Data Management/data Science Professionalsmentioning
confidence: 99%
“…In Australia, it is known that large-scale clinical studies have tended to move towards electronic data capture (EDC) systems or have accumulated implementation expertise with IT systems more rapidly than smaller-scale clinical studies. 5 For small studies, it is more likely to see a continued presence of traditional paper-based data capture methods as a perceived effective strategy. As the same requirements are necessary in Australia regardless of the study design or clinical focus, small-scale clinical studies need to consider the additional costs that operating an EDC system may incur for staff training, maintenance, support, hardware, and security requirements.…”
Section: History Of the Profession In Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers conducting trials are required to meet ethical and scientific standards for conducting and reporting trials that include the collection of high quality data (204,205). To help ensure compliance with these guidelines, high quality data monitoring and adherence to trial procedures is recommended (204). Qualitative research can help to understand how trial processes such as data monitoring are enacted.…”
Section: Findings and Contribution Of The Qualitative Researchmentioning
confidence: 99%
“…Qualitative research can help to understand how trial processes such as data monitoring are enacted. It can help to assess fidelity to trial processes and procedures and to identify and overcome obstacles to good practice (28,165,203,204).…”
Section: Findings and Contribution Of The Qualitative Researchmentioning
confidence: 99%